The Implementation of Forestry Police in Preventing Forest Encroachment in the Forest Area of ​​Jeneponto Regency - Asikin Muchtar (Fakultas Pertanian, Universitas Indonesia Timur, 2021)
This study aims to analyze the implementation of the Forestry Police's duties in preventing forest encroachment in the forest area of ​​Jeneponto Regency, and to analyze the efforts of the Forestry Police in preventing forest encroachment in the forest area of ​​Jeneponto Regency. This type of research is a survey research by conducting direct reviews to the research location. Questionnaires were distributed to informants to find out the implementation of the Forestry Police. The results of the study indicate that the Forestry Police have carried out their authority as mandated by Law Number 41 of 1999 concerning Forestry, but in its implementation the authority of the Forestry Police cannot carry out its duties and authorities optimally, this can be seen from the case of forest encroachment which is already concerning, namely almost all forested sub-districts have been encroached by 98.84%, this is due to internal factors, namely the lack of forestry police personnel guarding the forest area covering 7,120.87 ha, and external factors, namely the condition of the community around the forest area is relatively poor, the perpetrators of forest encroachment are mostly uneducated so that it greatly influences forest encroachment. The efforts of the Forestry Police in preventing criminal acts of forest encroachment in the forest areas of Jeneponto Regency are pre-emptive efforts, namely conducting socialization through outreach activities and approaches to the community, preventive efforts, namely conducting routine patrol activities in and around forest areas and patrols in forest areas, conducting surprise patrols in situational areas that receive sudden reports from the community, and special patrols that aim to carry out special tasks, such as patrols in special areas for repressive purposes to prevent forest encroachment activities, as well as repressive efforts, namely actions taken by the Forestry Police to process perpetrators of forest encroachment.